Modelling of acid mine drainage (AMD) in columns - Bernardes de Souza,C. M. (2011)
A model is proposed in this paper to describe the generation of acid mine drainage (AMD) in leaching columns. The model considers: (i) Water flow through the column, which is calculated using the 1 - D analytic solution of the Richards' equation assuming the existence of a similarity relationship between the water retention function and the water content profiles at a given time; and (ii) Pyrite oxidation weighted by microbiological effects occurring in spherical particles according to the shrinking core model. Mass balances of oxygen and pyrite were derived in order to evaluate the intrinsic oxidation rate and the pyrite fraction reacted with time and column position. The model was used to simulate a six month operation of a leaching column, which comprised successive weekly cycles of dry and wet periods. Simulation results demonstrated that AMD generation is strongly affected by the presence of microorganisms. A relative deviation of 5% between simulation and experimental data was obtained.